Factors associated with HIV testing among people who inject drugs Tehran - Noroozi, M.; Noroozi, A.; Farhoudian, A.; Mohammadi, F.; Higgs, Peter; Rahmani, A.; Sharifi, H.; Ghiasvand, H.; Fadai, F.; Abassi, M.; Armoon, B. (Informa Healthcare, 2017)
© 2017 Taylor & Francis Group, LLC Background: Little published research have assessed factors predicting the uptake of HIV-testing services for people who inject drugs (PWID) in Iranian settings. The objectives of the present study were to determine factors associated with HIV testing uptake among PWID in Tehran. Methods: We surveyed 500 PWID in Tehran concerning demographic characteristics, drug-related and sexual risk behaviors, and HIV testing. HIV-related stigma variables were assessed using a scale consisted of 22 agree/disagree statements in three subscales including shame/blame/isolation, perceived discrimination, and equity. We used multivariate logistic regression to identify factors associated with HIV testing. Results: Participant ages ranged from 19 to 67 years. Multivariable model shows that factors independently associated with recent HIV testing included level of education (adjusted odds ratios [aOR] 1.12, 95% CI 1.44–4.42), living status (aOR 1.91, 95% confidence interval [CI] 1.35–2.71), income (aOR 1.64, 95% CI 1.18–2.29), length of injecting career (aOR 1.3, 95% CI 1.2–2.23), and perceived risk of HIV infection (aOR 0.51, 95% CI 1.18–0.88). There was a statistically significant relationship between lower level of HIV-related stigma and HIV testing among PWID (OR 2.78, 95% CI 1.15–5.2). Conclusions: These findings suggested a need to strengthen current HIV testing programs by social support and reducing HIV-related stigma. It is also important to modify the atti tude of the public toward people living with HIV/AIDS.